Fazlur Rahman: Esensi Pendidikan Islam - Dinata, Syaiful; Latipah, Eva; Izzah, Ismatul (Research in Education and Technology (REGY), 2023)
Islamic education should not only be a process of transmitting material, but far from it, integrated into the personality and become a guide in the activities of daily life. Fazlur Rahman is one of the reformers of Islam who incised his thoughts on the modernity of Islamic education. His ideas include the basics of Islamic education, namely the Qur'an and Sunnah, the goal of Islamic education is to form a morally and intellectually intact human being, the education system integrates general knowledge and religion. Education curriculum with a double movement and mastery of language. The method of writing is descriptive analysis with a library research approach. Analyze the data collected through books or scientific journals, then describe them. The result of his research is that the essence of Islamic education from Fazlur Rahman's perspective is the growth of original and adequate Islamic thought. Then, Fazlur Rahman said that the most important thing about Islamic education is its essence and as Islamic intellectualism, because for him this is what is meant as the essential essence of Islam itself.